2007
DOI: 10.1111/j.1399-6576.2007.01263.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined intrathecal and epidural magnesium sulfate supplementation of spinal anesthesia to reduce post‐operative analgesic requirements: a prospective, randomized, double‐blind, controlled trial in patients undergoing major orthopedic surgery

Abstract: In patients undergoing orthopedic surgery, supplementation of spinal anesthesia with combined intrathecal and epidural MgSO(4) significantly reduces patients' post-operative analgesic requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 42 publications
12
119
1
Order By: Relevance
“…Although the mechanism of analgesia produced by magnesium is not fully understood, many authors have reported that magnesium is associated with a reduced analgesic requirement and less discomfort in the postoperative period via different routes of administration. 7 Most of these studies have investigated systemic 9 or neuraxial, 7,8 administration of magnesium, whereas studies on the administration of magnesium for peripheral nerve block are scarce. 10 The present randomized controlled study was performed to evaluate the effect of adding magnesium sulphate to long-acting local anesthetics (i.e., bupivacaineepinephrine mixture) for interscalene nerve block.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of analgesia produced by magnesium is not fully understood, many authors have reported that magnesium is associated with a reduced analgesic requirement and less discomfort in the postoperative period via different routes of administration. 7 Most of these studies have investigated systemic 9 or neuraxial, 7,8 administration of magnesium, whereas studies on the administration of magnesium for peripheral nerve block are scarce. 10 The present randomized controlled study was performed to evaluate the effect of adding magnesium sulphate to long-acting local anesthetics (i.e., bupivacaineepinephrine mixture) for interscalene nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism for the analgesic action of magnesium is the voltage-dependent antagonism of NMDA receptors, leading to the prevention of central sensitization from peripheral nociceptive stimulation and a decrease in acute pain after tissue injury. In several investigations [7][8][9] showing effective analgesia due to magnesium sulphate, magnesium was administered via the intravenous or neuraxial route so access to NMDA receptors was probable. However, involvement of NMDA receptors in peripheral blocks is less certain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When used with local anaesthetic, it resulted in prolongation of analgesia without significant complication (23,24).This prolongation of anaesthesia is consistent with the experimental synergistic action between spinal local aneasthetic and NMDA antagonists like magnesium sulphate, which use anti -nociceptive effects via different mechanisms; (25,26,27) hence the rationale for combining the two. There are no selective NMDA receptor antagonists available for pain management; hence, drugs with other clinical uses, such as magnesium sulphate and ketamine, shown promises as analgesics, have been used.…”
Section: Discussionmentioning
confidence: 66%
“…9 Owing to the lower affinity of the S (-) isomer to the cardiac sodium channels compared to the R (+) isomer, it is associated with less cardiac side effects. 10,11 Arcioni et al 12 observed that intrathecal and epidural Magnesium Sulphate potentiated and prolonged motor block. They concluded that patients undergoing orthopaedic surgery, supplementation of spinal anaesthesia with combined intrathecal and epidural MgSO4 significantly reduces post-operative analgesic requirements.…”
Section: Discussionmentioning
confidence: 99%